Stunting Sistem Cerdas Mendiagnosa Stunting pada Anak Menggunakan Mesin Inferensi - Tugiono; Afdal Alhafiz; Hafizah (Jurnal Informasi dan Teknologi, 2022)
Stunting is an unresolved nutritional problem in Indonesia. Stunting is a physical growth disorder characterized by a decrease in growth speed and is the impact of nutritional imbalances. Stunting will cause long-term impacts, namely disruption of physical, mental, intellectual, and cognitive development. Children who are stunted until the age of 5 years will be difficult to repair so that it will continue into adulthood and can increase the risk of offspring with low birth weight. Low economic factors cause people to think twice about consulting on stunting with doctors or nutritionists. In addition, the reluctance to come to the Puskesmas is an indicator of the low level of public awareness of children's health. Whereas the Puskesmas is a place that provides information about the problem of stunting. This is one of the causes of the delay in reducing the prevalence of stunting. An expert system is a system that seeks to adopt human abilities or knowledge into computers, so that computers can work in solving a problem like an expert or someone who has knowledge in a particular field. Utilization of expert systems with certainty factor methods and forward chaining inference engines will greatly help facilitate the community in making an early diagnosis of stunting in children, so that people can take initial treatment if their child is diagnosed with stunting. With this facility, of course, the risk of increasing stunting in children can be reduced and even prevention is carried out.